2016
DOI: 10.1017/s1479262116000150
|View full text |Cite
|
Sign up to set email alerts
|

Breeding medicinal plant, periwinkle [Catharanthus roseus(L) G. Don]: a review

Abstract: Periwinkle [Catharanthus roseus (L) G. Don] has become one of the very extensively investigated medicinal plants after the discovery of two powerful anti-cancer alkaloids, vinblastine and vincristine, in its leaves more than 50 years ago. These alkaloidal drugs are still in clinical use. Also, periwinkle is still the only source of these alkaloids and their precursors, catharanthine and vindoline. Low concentrations of these alkaloids in the plant and, therefore, high costs of their extraction have led to trem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 104 publications
(176 reference statements)
1
8
0
1
Order By: Relevance
“…2). Similar diploid chromosome numbers were reported earlier which correlates to the present study (7,8,(20)(21)(22)(23) . The consistency in the number of diploid chromosome complement indicated that this species is stable.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…2). Similar diploid chromosome numbers were reported earlier which correlates to the present study (7,8,(20)(21)(22)(23) . The consistency in the number of diploid chromosome complement indicated that this species is stable.…”
Section: Resultssupporting
confidence: 93%
“…Moreover, a few abnormal cells with 2n = 12 and 14 chromosomes were also reported for this species, which did not correlate with the present findings (24) . Some previous workers reported the 16 chromosomes of pink and white flower types with the different centromeric positions (21,22) . However, in the present study, 16 metacentric chromosomes were found in both pink and white flower type of C. roseus (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is certain that GS will be able to accelerate breeding of various crops that have been neglected so far. To meet the recent demand for using indigenous crops, such as minor cereals (Hinterthuer, 2017 ), local vegetables (Cernansky, 2015 ), bioenergy crops (Allwright and Taylor, 2016 ), medicinal plants (Kulkarni et al, 2016 ), and forage crops (O'Mara, 2012 ; Kingston-Smith et al, 2013 ), the breeding of various crop species will be required (Abberton et al, 2016 ). GS is expected to improve mass selection of allogamous crops, to which many crops mentioned above belong, because it accelerates mass selection cycles (Yabe et al, 2013 ) and allows the selection of good paternal parents before pollination even for seed yield relating traits (Yabe et al, 2014b ).…”
Section: Introductionmentioning
confidence: 99%
“…Plant extract can help treat dysentery and diarrhoea (ICMR, 2007 5:813-859). For further details see Kulkarni et al (2016).…”
Section: Catharanthus Roseus Gdon Periwinklementioning
confidence: 99%